Dyeing process optimization of chitosan modified cotton dyed with Bixa orellana and Caesalpinia sappan - Rachma Tia Evitasari; Zahrul Mufrodi (Universitas Ahmad Dahlan, 2021)
Indonesia is rich in flora diversity, very potential for the development of natural dyes. The advantage of dyeing fabrics with natural dyes is that they contain antioxidants and environmentally friendly. The purpose of this study was to optimize the dyeing process on chitosan-modified fabrics with variations in temperature and solution ratio. The dyes used were kesumba keling seeds (Bixa Orellana) and sappan wood (Caesalpinia sappan). The analysis carried out is the analysis of the value of color differences (DE), calculated to determine changes in color intensity. The dyed fabrics were tested for fastness to light, heat, and washing. The best value of DE was obtained at a temperature variation of 70 oC and a ratio of fabric weight to volume of solution 1:75 for both dyes from kesumba keling seeds and sappan wood with each DE value of 6.22 and 11.84. Supported by the test results of fastness to sunlight and iron heat which gives good results.